ANALISIS KEPUASAN SIVITAS AKADEMIKA TERHADAP PELAYANAN PENYELENGGARAAN PENDIDIKAN - Feri Setyowibowo; Anton Subarno (PAEDAGOGIA, 2010)
In the globalization era such today, the competition to get customer is gettingtougher, making companies more aggressive in giving the best service to their customersthrough many alternatives and more innovative ways. Faculty of Teacher Training andEducation of Sebelas Maret University, a faculty that provides professional educator, isreaching out for the best and more inovative ways to serve its customers. In this descriptiveresearch,the population were students and lecturers in amount of 3,470, in which100 respondents (5%) of the population as the samples.The faculty staff has already had agood performance, hence it made the high satisfactions to students and lecturers. Thesesatisfactions were reflected by the items no 1,4,5,6,7,14 that in the quadrant II. By theseresults, those were the items that should be maintained and improved.